2010
DOI: 10.1111/j.1540-8159.2009.02661.x
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Assisted Wound Closure for Pacemaker Infection

Abstract: When the risk of total system explantation is high, less-invasive VAC might serve as the option for treating an infected pacemaker. (PACE 2010; 426-430).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
6
1
Order By: Relevance
“…Compared to our patients, the duration of V.A.C. treatment was shorter (19.5 days vs 34.4 days) in the study of Satsu and Onoe 12 . This is explained by the fact that we continued V.A.C.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Compared to our patients, the duration of V.A.C. treatment was shorter (19.5 days vs 34.4 days) in the study of Satsu and Onoe 12 . This is explained by the fact that we continued V.A.C.…”
Section: Discussioncontrasting
confidence: 73%
“…So far, only one publication by Satsu and Onoe describes the treatment of CD‐infections with a V.A.C. system 12 . In this study, four patients with a CD‐infection were successfully treated with a V.A.C system.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In 2010, Satsu et al reported the use of a vacuum‐assisted wound closure (VAC) system as an option for treating an infected device [34]. The VAC system is comprised of polyurethane foam with an evacuation tube, a vacuum pump, and adhesive drape.…”
Section: Recent Studiesmentioning
confidence: 99%
“…-Placement of an antibiotic-releasing envelope to treat an infected pacemaker pocket: only one case report has been described in the literature (Lopez, 2010), with good results. -Vacuum-assisted system for pacemaker infection: Satsu & Onoe (2010) describe the application of vacuum-assisted therapy for treating four patients with infected permanent pacemaker with good results.…”
Section: Surgical Lead Removal and Other Techniquesmentioning
confidence: 99%